Investigating the Effect of Effective Factors on Actual Purchase with the Mediating Role of Purchase Intention and the Moderating Role of Iranian Product Type - Aliakbar Shahri Mejarshin; Alireza Rousta; Abdullah Naami (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The primary purpose of this study is to investigate the factors affecting the actual or final purchase of Iranian goods by evaluating the mediation effect of purchase intention and the moderating role of Iranian product type. Methodology: This research is an applied goal in terms of a quantitative research approach and has a descriptive survey strategy. The statistical population of this study is all customers and consumers of Iranian clothing and home appliances in the East Azarbaijan province of Tabriz, of which 377 people were calculated and selected as a sample by G-Power software. The data collection tool is a questionnaire, and the structural equation model with Smart Pls software has been used to analyze the data. Findings: The results show that product knowledge, perceived quality, and perceived value positively and significantly affect the intention to buy Iranian goods. Also, the variables of product knowledge and perceived value positively and significantly affect the actual purchase of Iranian goods. Contrary to the research results, the perceived quality variable does not positively impact actual purchases substantially. The mediating role of the purchase intention variable was confirmed for the relationship between product knowledge and perceived value with the actual purchase. The product type variable only modulates the causal relationship between product knowledge and actual purchase. This section presents the study's main findings (usually with statistical significance). Originality/Value: This research provides accurate and precise information about consumers' attitudes toward Iranian goods. These results can be a roadmap for manufacturers to strengthen and improve the market share of Iranian goods by increasing the quality, providing knowledge about the performance of Iranian goods, and increasing confidence.